2019
DOI: 10.1108/nfs-03-2019-0090
|View full text |Cite
|
Sign up to set email alerts
|

Honey as a functional additive in yoghurt – a review

Abstract: Purpose Recent societal interest in healthful foods has led to the development of functional dairy products that basically provide health benefits in addition to their fundamental nutrients. Yoghurt being most popular fermented milk product due to its healthy image can be an excellent carrier for probiotics. Functional properties of yoghurt can be enhanced with the inclusion of functional ingredients such as probiotics and its conjugate application with prebiotics may be advantageous as it favors probiotic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The emergence of functional dairy products, which essentially offer health advantages in addition to their basic ingredients, is a result of the recent public interest in healthier diets. Due to its positive connotations with health, yoghurt is the most widely consumed fermented milk product [25]. The addition of honey increases the nutritional value of yoghurt.…”
Section: Honey As a Functional Ingredient In Yoghurtmentioning
confidence: 99%
“…The emergence of functional dairy products, which essentially offer health advantages in addition to their basic ingredients, is a result of the recent public interest in healthier diets. Due to its positive connotations with health, yoghurt is the most widely consumed fermented milk product [25]. The addition of honey increases the nutritional value of yoghurt.…”
Section: Honey As a Functional Ingredient In Yoghurtmentioning
confidence: 99%
“…It was determined in clinical studies that L. acidophilus LA-5, B.lactis BB-12 and B.longum probiotic cultures are balanced in honey and that honey could be consumed as a functional food with yoghurt (Sarkar and Candra, 2019). It is indicated that methyl glyoxal content of the honey from manuka tree in New Zealand is good for gastroenterological system disorders (Yeşilada, 2019).…”
Section: Studies On Honey As a Functional Foodmentioning
confidence: 99%
“…Functional food is the general description of the foods creating positive results for a certain function in human metabolism, a certain organ or a certain disease beside its nutrition property, healing, bearing curative or risk reduction features in diseases, beneficial for human health in short (Sarkar and Candra, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This plaque may rupture and lead to clot formation due to platelet activation, possibly closing the vessel completely, causing a heart attack 15 . The nutritional and medicinal value of honey combined with the presence of oligosaccharides has projected honey as a functional additive in fermented milk 16 . In addition, it is used as a sweetener and as a preservative in dairy products 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The growing market for this honey type significantly contributes to its increased price; however, consumers increasingly appreciate the taste and nutritional value of honeydew honey 23 . According to the literature reports, honey is mainly added to yogurt 10 , 16 , 17 . The addition of honey, especially honeydew honey to kefir, is not commonly described in the literature.…”
Section: Introductionmentioning
confidence: 99%